Relationships between fauna and people and the role of ethnozoology in animal conservation - Alves, Rômulo Romeu Nóbrega (Ethnobiology and Conservation, 2012)
Faunal resources have played a wide range of roles in human life from the earliest days of recorded history. In addition to their utilitarian importance, animals have been recognized in religion, art, music and literature and other different cultural manifestations of mankind. Animals uses and the means by which they are exploited by humans, as well as the cultural aspects which conduct interactions between people and animals, are implicated in a lower or higher pressure on populations of exploited species, reflected in either their sustainable use or even lead to their extinction. The variety of interactions between humans and animals is the subject matter of ethnozoology - the branch of ethnobiology that investigates the knowledge human societies have accumulated concerning animals, as well as their significance to those people and their uses. Ethnozoological studies can be a valuable asset to increase our understanding of the cultural, economic, social, and traditional roles of played by animals. In this context, they have a central role in conservation and management. This work provides a brief review on the main forms of interactions between humans and the fauna along history, and their ecological implications, and discusses the role of the ethnozoology in animal conservation.